2016
DOI: 10.1186/s12974-016-0666-8
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet feeding differentially affects the development of inflammation in the central nervous system

Abstract: BackgroundObesity and its associated disorders are becoming a major health issue in many countries. The resulting low-grade inflammation not only affects the periphery but also the central nervous system. We set out to study, in a time-dependent manner, the effects of a high-fat diet on different regions of the central nervous system with regard to the inflammatory tone.MethodsWe used a diet-induced obesity model and compared at several time-points (1, 2, 4, 6, 8, and 16 weeks) a group of mice fed a high-fat d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 64 publications
11
96
2
Order By: Relevance
“…Given the lack of a peripheral inflammatory response in HFD-fed mice, we subsequently investigated the impact of a HFD on hypothalamic inflammatory markers. Consistent with previous studies (Andre et al, 2017; Baufeld et al, 2016; Buckman et al, 2015; Gao et al, 2017; Gao et al, 2014; Guillemot-Legris et al, 2016; Nadjar et al, 2017; Thaler and Schwartz, 2010; Thaler et al, 2012; Valdearcos et al, 2017; Valdearcos et al, 2014) we found that gene expression of the pro-inflammatory cytokine genes IL1β, IL6 and TNFα, as well as chemokine genes CCL2 and CCL5 was significantly increased in HFD-fed mice compared to SD-fed mice (Fig. 2A-E).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Given the lack of a peripheral inflammatory response in HFD-fed mice, we subsequently investigated the impact of a HFD on hypothalamic inflammatory markers. Consistent with previous studies (Andre et al, 2017; Baufeld et al, 2016; Buckman et al, 2015; Gao et al, 2017; Gao et al, 2014; Guillemot-Legris et al, 2016; Nadjar et al, 2017; Thaler and Schwartz, 2010; Thaler et al, 2012; Valdearcos et al, 2017; Valdearcos et al, 2014) we found that gene expression of the pro-inflammatory cytokine genes IL1β, IL6 and TNFα, as well as chemokine genes CCL2 and CCL5 was significantly increased in HFD-fed mice compared to SD-fed mice (Fig. 2A-E).…”
Section: Resultssupporting
confidence: 92%
“…Since 2012, several studies have shown that HFD consumption induces astrogliosis and microgliosis in the arcuate nucleus (ARC) of the HT (Andre et al, 2017; Balland and Cowley, 2017; Baufeld et al, 2016; Gao et al, 2014; Guillemot-Legris et al, 2016; Kim et al, 2019; Thaler et al, 2012; Valdearcos et al, 2017; Valdearcos et al, 2014). The microglia activation that is induced by lipids and connects dietary fat and brain inflammatory signaling is begging to be seen as the missing link between the hypothalamic response to HFD and susceptibility to obesity (Andre et al, 2017; Kim et al, 2019; Valdearcos et al, 2017; Valdearcos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we again suggest that other mechanisms, independent of adenosine may be participating, such as blood-brain barrier regulation by pro-inflammatory cytokines (as hypothesized in [33]). Indeed it has been shown that the cerebellum seems to be prone to high-fat diet induced neuroinflammation mediated by the endogenous synthesis of the inflammatory mediators monocyte chemo attractant protein-1 (MCP-1), interleukin 1β (IL-1β), tumor necrosis factor-α (TNFα), and cyclooxygenase-2 (COX-2) as compared to the cerebral cortex [36]. In the case of the infection with the attenuated rabies virus CVS-F3 it has been shown that increased cerebellar blood-brain barrier permeability is accompanied by increased local synthesis of TNFα, interferon γ (IFNγ), and intercellular adhesion molecule-1 (ICAM-1) and occurs earlier in the cerebellum than in the cerebral cortex [37].…”
Section: Discussionmentioning
confidence: 99%
“…cDNA was synthesized from 1 mg of total RNA using the GoScript Reverse Transcription System (Promega, Madison, WI, USA). qPCR was performed in duplicate for each sample using a SYBR Green mix (GoTaq qPCR Master Mix; Promega) with a STEP one PLUS instrument and software (Applied Biosystems, Foster City, CA, USA) as previously described (26). Products were analyzed by performing a melting curve at the end of the PCR reaction.…”
Section: Mrna Extraction and Real-time Qpcrmentioning
confidence: 99%